Order parameter phase locking as a cause of a zero bias peak in the differential tunneling conductance of bilayers with electron-hole pairing - Bezuglyj, A.I.; Shevchenko, S.I. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
In n—p bilayer systems an exotic phase-coherent state emerges due to Coulomb pairing of n-layer electrons with p-layer holes. Unlike Josephson junctions, the order parameter phase may be locked by matrix elements of interlayer tunneling in n—p bilayers. Here we show how the phase locking phenomenon specifies the response of the electron—hole condensate to interlayer voltages. In the absence of an applied magnetic field, the phase is steady-state (locked) at low interlayer voltages, V < Vc, but the phase increases monotonically with time (is unlocked) at V > Vc. Thechange in the system dynamics at V=Vc gives rise to a peak in the differential tunneling conductance.The peak width Vc is proportional to the absolute value of the tunneling matrix element |T12| , but its height does not depend on |T12| ; thus the peak is sharp for small |T12| . An in-plane magnetic field reduces the peak height considerably. The present results are in qualitative agreement with the zero-bias peak behavior that has recently been observed in bilayer quantum Hallpseudoferromagnets with spontaneous interlayer phase coherence.